A multifunctional magnetic material based on a solid solution of Fe(ii)/Co(ii) complexes with a macrocyclic cyclam-based ligand - Drahoš, Bohuslav; Šalitroš, Ivan; Císařová, Ivana; Herchel, Radovan (Dalton transactions (Cambridge, England, 2021)
In order to prepare a multifunctional magnetic material combining spin crossover together with single-molecular magnetism, co-crystallization of Fe(ii) and Co(ii) complexes of the pyridine derivative of cyclam (Py2-C = 1,8-bis(pyridin-2-ylmethyl)-1,4,8,11-tetraazacyclotetradecane) was performed. Complexes with the general formula [MII(Py2-C)](ClO4)2·H2O (MII = Fe (1), Co (2) or Fe0.4Co0.6 (3)) were prepared and thoroughly characterized. Based on X-ray molecular structures, they formed octahedral complexes with cis-arrangement of the coordinated pyridine moieties. Magnetic data revealed that the Fe(ii) complex 1 shows complete SCO with the transition temperature T1/2 = 141 K, which is preserved also in the mixed Fe/Co system 3 (T1/2 = 128 K). Co(ii) complex 2 behaves as a field-induced single-molecule magnet as well as the mixed system 3 with a direct and phonon bottleneck relaxation process, respectively. This is the first example of such Fe/Co solid solution providing SCO in combination with field-induced SMM properties. Unfortunately, the light-induced excited spin-state trapping (LIESST) effect was not observed either for the Fe(ii) complex 1 or the mixed system 3 and thus, the effect of SCO on SMM properties at low temperature could not be investigated in detail. Nevertheless, the obtained results clearly document the success of the solid solution methodology for the preparation of multifunctional magnetic materials.